Discovery of a selective PI3Kα inhibitor via structure-based virtual screening for targeted colorectal cancer therapy - Hussam Albassam; Omar Almutairi; Majed Alnasser; Faisal Altowairqi; Faris Almutairi; Saad Alobid (Journal of Enzyme Inhibition and Medicinal Chemistry)
Colorectal cancer (CRC) remains a leading cause of cancer-related mortality globally, driving an urgent need for effective therapies. A promising avenue of research focuses on the PI3K/AKT/mTOR signalling pathway, which is frequently disrupted by mutations in the PI3Kα subunit. Our cutting-edge study employed a structure-based virtual screening of ∼3000 compounds, leading to the discovery of F0608-0019, a highly potent and selective PI3Kα inhibitor. F0608-0019 demonstrated remarkable efficacy in suppressing HCT116 colorectal cancer cell proliferation, with an IC50 of 12.14 µM, while maintaining high selectivity by minimising activity against other PI3K isoforms. Advanced molecular dynamics simulations highlighted the stability of F0608-0019’s binding interactions with key amino acids, such as TRP:780, ILE:932, and VAL:850, which are critical for its targeted action. These exciting findings reveal F0608-0019 as a leading candidate for innovative CRC therapies that selectively target PI3Kα dysregulation, offering promising new possibilities for effective CRC treatment.